(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
The main objective of the research is to identify the nature of the organizational structure in the quality of labor relations at the Kalamoun General Hospital in the city of Nabek and the Kalamoun Private University Hospital. In order to achieve this goal, the quantitative entry and the distribution of a sample size of 357, the study reached a number of results, the most important of which are: • A statistically significant effect of the organizational structure with its dimensions (formal, complexity, communication) on the quality of labor relations in both hospitals under study. • The general impact of the organizational structure on the quality of labor relations in various disciplines, and psychology at Al-Kalamoun Hospital (public and private). • There are numbers statistically in the nature of the organizational structure in the nature of work in the following variables (type of hospital, gender, job age, and years of service).